Analisis Kesalahan Hasil Belajar Mahasiswa pada Operasi Matriks Mata Kuliah Aljabar Linear dan Matriks - Iim Marfu’ah; Heriyati Heriyati (Departement of Mathematics Education, 2023)
In solving math problems, students including many students experience difficulties, so there is a high probability of experiencing errors in answering questions. This study aims to analyze student errors in solving mathematical problems in matrix material, linear algebra and matrix courses and describe student learning outcomes errors in linear algebra and matrix courses, then identify factors that affect student learning outcomes errors in linear algebra and matrix courses. This type of research is qualitative descriptive research with a case study method. Sampling was done using purposive sampling technique with tests and interviews. The sample of this study consisted of 37 4th semester students who had an average that was still below the limit of completeness in mathematics courses in the previous semester. The results showed that the factors that influence student learning outcomes errors are a) less careful in understanding the problem, b) lack of time management when working on problems, c) lack of focus when working, d) lack of mastery of concepts, formulas and calculation procedures in matrix operations, e) lack of mastery of basic mathematical operations, f) lack of caution and thoroughness.